2020
DOI: 10.1523/jneurosci.1832-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Neurokinin-1 Receptor is Expressed with Gastrin-Releasing Peptide Receptor in Spinal Interneurons and Modulates Itch

Abstract: The neurokinin-1 receptor (NK1R, encoded by Tacr1) is expressed in spinal dorsal horn neurons and has been suggested to mediate itch. However, previous studies relied heavily on neurotoxic ablation of NK1R spinal neurons, which limited further dissection of their function in spinal itch circuitry. Thus, we leveraged a newly developed Tacr1 CreER mouse line to characterize the role of NK1R spinal neurons in itch. We show that pharmacological activation of spinal NK1R and chemogenetic activation of Tacr1 CreER s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 74 publications
(138 reference statements)
1
22
1
Order By: Relevance
“…However, another group showed that SP activated MRGPCR on sensory neurons to induce itching in mice [149,150]. NK1R is expressed in the DRG, spinal horns, and brain areas responsible for itch signaling [151][152][153], and a recent study demonstrated that spinal NK1R neurons mediate itching in mice [152]. In line with the findings above, NK1R may have a central role in potentiating pruritus from the periphery to the spinothalamic tract and then to the brain cortex.…”
Section: Neuropeptidesmentioning
confidence: 53%
See 1 more Smart Citation
“…However, another group showed that SP activated MRGPCR on sensory neurons to induce itching in mice [149,150]. NK1R is expressed in the DRG, spinal horns, and brain areas responsible for itch signaling [151][152][153], and a recent study demonstrated that spinal NK1R neurons mediate itching in mice [152]. In line with the findings above, NK1R may have a central role in potentiating pruritus from the periphery to the spinothalamic tract and then to the brain cortex.…”
Section: Neuropeptidesmentioning
confidence: 53%
“…Significant amounts of sensory neurons express SP or GRP [151]. Additionally, GRP is a crucial spinal neurotransmitter for itch [170], and the latest study showed that spinal dorsal horn NK1R neurons, which are responsible for spinal pruritus, contained GRPR [152], and upregulation of serum neurotensin levels and gene expression in the lesioned skin of patients with AD. The possible interaction between neurotensin and MCs may contribute to the pathogenesis of AD [171].…”
Section: Neuropeptidesmentioning
confidence: 99%
“…However, chemogenetic and optogenetic stimulation of Tacr1 spinal projection neurons (Deng et al, 2020 ; Barik et al, 2021 ) drive spontaneous pain-induced protective behaviors and suppress itch (Barik et al, 2021 ). In an independent study, chemogenetic activation of Tacr1 neurons promoted itch and lacked spontaneous pain behaviors (Sheahan et al, 2020 ). This contradiction can be explained due to the usage of different genetic strategies to target the Tacr1 population.…”
Section: Interactions Between Pain and Itch In The Spinal Projection ...mentioning
confidence: 99%
“…A critical factor for successful delivery and expression of fluorescent proteins is the serotype of virus. In spinal cord research, anterogradely transporting AAVs containing the genome of serotype 2 packaged in capsids from serotypes 1, 2, 5, 8, or 9 (AAV2/1, AAV2/2, AAV2/5, AAV2/8, AAV2/9) have been routinely used for the manipulation of spinal neurons or ascending pathways ( Dougherty et al., 2013 ; Fink et al., 2014 ; Bourane et al., 2015 ; Foster et al., 2015 ; Ruder, Takeoka and Arber, 2016 ; Choi et al., 2020 ; Sheahan et al., 2020 ; Barik et al., 2021 ; Gatto et al., 2021 ) ( Figures 1 A and 1B), while AAV retro ( Tervo et al., 2016 ), which is a capsid variant of AAV2, is used for targeting descending neurons ( Esposito et al., 2014 ; Basaldella et al., 2015 ; Murray et al., 2018 ; Sathyamurthy et al., 2020 ; Usseglio et al., 2020 ) ( Figure 1 C). For more information on AAVs, please refer to the following reviews ( Li et al., 2020 ; Naso et al., 2017 ; Samulski and Muzyczka, 2014 ; Wang et al., 2019 ).…”
Section: Before You Beginmentioning
confidence: 99%
“…
Figure 1 Intraspinal delivery of viral vectors presents a powerful approach for addressing basic questions regarding the organization and function of spinal circuits Genetically-defined groups of spinal neurons and the circuits that they are embedded in can be manipulated using two different groups of AAVs – anterogradely transporting (A and B) and retrogradely transporting AAVs (C). By injecting recombinant anterogradely transporting AAVs into different segments of the spinal cord in wildtype mice or genetic reporter lines, it is possible to acutely manipulate select spatially defined populations of spinal neurons, specifically in adulthood ( Dougherty et al., 2013 ; Fink et al., 2014 ; Bourane et al., 2015 ; Foster et al., 2015 ; Ruder, Takeoka and Arber, 2016 ; Choi et al., 2020 ; Sheahan et al., 2020 ; Barik et al., 2021 ; Gatto et al., 2021 ) (A). By combining spinal injections of anterogradely transporting AAVs with stereotactic injections of retrogradely transporting AAVs in brain regions that are targeted by ascending spinal neurons, and/or by the placement of optic fibers or drug cannulae in specific brain regions, it is possible to manipulate ascending pathways in a circuit-specific manner ( Conner et al., 2021 ; Fink et al., 2014 ; Bouvier et al., 2015 ; François et al., 2017 ; Sheahan et al., 2020 ) (B).
…”
Section: Before You Beginmentioning
confidence: 99%